Measuring agrifood systems: New indicators and global estimates - Thurlow, James; Holtemeyer, Brian; Jiang, Shiyun; Pauw, Karl; Randriamamonjy, Josee (International Food Policy Research Institute, 2025)
Transformation of the agrifood system is a cornerstone of many governments’ national development plans. This reflects the importance of agrifood systems for the livelihoods and wellbeing of poor populations as well as the continued strong association of agricultural transformation with longer-term economic development and structural change. Agrifood transformation is also key to healthier diets and more sustainable production systems. However, adopting an agrifood system perspective is not trivial—it requires looking “beyond agriculture” when prioritizing policies and tracking outcomes by also considering upstream and downstream agrifood-related activities, such as agro-processing and food distribution. Measuring transformation therefore requires economywide data and innovative metrics. This study introduces two such metrics: AgGDP+, which captures the total value-added across the on- and off-farm sectors of the agrifood system, and AgEMP+, which reflects the employment generated across its various components. It further explains how consistent estimates of AgGDP+ and AgEMP+ were produced for 211 and 186 countries, respectively, over the period between 2000 and 2021, and demonstrates how this Agri-Food System Dashboard—a publicly available resource—can be used to monitor transformation, prioritize investments, and better understand the evolving role of agrifood systems in national economies or at regional or global scales.